Characterization of phytochemical components and identification of main antioxidants in Crateva unilocalaris Buch. shoots by UHPLC-Q-Orbitrap-MS2 analysis. (May 2021) - Ma, Qian; Cai, Shengbao; Liu, Xiaojing; Shi, Jiyuan; Yi, Junjie
Graphical abstract: Highlights: Six phenolics and seven saponins were detected in Crateva unilocalaris shoots. Chikusetsusaponin IVa and chlorogenic acid were the main phytochemicals. Acetone extract had the highest phenolic, saponin contents and antioxidant effect. All extracts exhibited good inhibitory effects on intracellular ROS in HepG2 cells. Phenolics but not saponins were the main antioxidants in 80% acetone extract. Abstract: The chemical constituents and antioxidant activity of the three different extracts (80% methanol, 80% ethanol, and 80% acetone) of Crateva unilocalaris Buch. shoots were investigated. Six phenolic compounds and seven saponins were characterized in all extracts. Chikusetsusaponin IVa had the highest content (17.92 to 29.16 mg/g), and chlorogenic acid was the most abundant phenolic compound (10.48 to 13.99 mg/g). The acetone extract had the highest total phenolic, flavonoid, and saponin contents and the strongest antioxidant activity. Moreover, all extracts exhibited good effects on the inhibition of intracellular ROS generation in HepG2 cells. Phenolic compounds but not saponins contributed significantly to the DPPH or ABTS radical scavenging activity of C. unilocalaris shoots according to the results of DPPH–UHPLC–HRMS and ABTS+–UHPLC–HRMS analyses. These results may be helpful for further understandings and utilization of C. unilocalaris shoots as a potential natural source in the food or nutraceuticals industry.